Influence of job satisfaction on employee organizational commitment in Serbian companies - Cvjetković, Milena; Cvjetković, Milovan (Ekonomija - teorija i praksa, 2023)
This paper presents research aimed at assessing the impact of job satisfaction on employee’s organizational commitment. The study involved a sample of 248 employees in Serbian companies. Correlation analysis revealed a statistically strong and significant relationship between job satisfaction and organizational commitment variables. Regression analysis identified that the nature of work and supervision variables made the most significant individual contributions to achieving organizational commitment. The T-test of independent samples on job satisfaction indicated a statistically significant difference in mean values concerning employee satisfaction based on years of service. The research findings offer insights for enhancing employee job satisfaction, consequently fostering organizational commitment, leading to increased engagement and improved work performance.